EXPLAIN EXPLAIN EXPLAIN ME PLS PLS
Attachments:
![](https://hi-static.z-dn.net/files/d39/4683aa34679119d7fc593d5954a5567d.jpg)
Answers
Answered by
2
Answer:
(a^m ÷ a^n = a^m-n)
Now,
7^2t ÷ 7^t+1 = 7^5
>7^2t-(t+1) = 7^5
>7^2t-t-1 = 7^5
Since the bases are same (all the base numbers are 7) , we can take the powers of the numbers into an equation so as to solve them.
Therefore,
2t - t -1 = 5
> t - 1 = 5
> t = 5 + 1
> t = 6
Similar questions
English,
3 months ago
Business Studies,
3 months ago
Math,
3 months ago
English,
7 months ago
Math,
1 year ago